Middle Bronze Age and Roman settlement at Manor Pit, Baston, Lincolnshire : excavations 2002-2014 - Atkins, Rob, 1968- (Archaeopress Archaeology, 2020)
Between 2002 and 2014 MOLA Northampton carried out evaluation and excavation work at the Manor Pit, Baston, Lincolnshire. The site saw significant occupation in the late Bronze Age and Roman periods, with evidence of enclosures in Medieval and Post-Medieval times.